Pengaruh Metode Gasing Terhadap Hasil Belajar Siswa pada Materi Penjumlahan Kelas IV SDN Tanjung Jati 2 - Ramadhan, Muhamad Zakhi; Setyawan, Agung; Widayati, Sih (maktab: Jurnal Pendidikan dan Teknologi, 2024)
The underutilization of learning strategies in education drives this investigation. The researchers at SDN Tanjung Jati 2 set out to do two things: first, provide a general outline of how the spinning approach was put into practice. Second, find out how the method affected the mathematical learning results of fourth graders. Using a one-group pretest-posttest design, this study combines a quantitative technique with an experimental approach. The twenty-one participants in this research are all fourth graders. Saturated sampling is the method used for the sampling process. Methods such as interviews, exams, and observation are used to gather data. A t-value of 18.71 and a t-table value of 2.09 were determined by the computations. The t-value must be higher than the t-table value in order to accept the alternative hypothesis (Ha) and reject the null hypothesis (Ho). The research found that learning addition via the spinning approach significantly improved learning outcomes. Compared to students who were taught just via lectures, those who were taught utilizing the spinning approach had much better learning results.